25 years of high-frequency ground penetrating radar measurements of snow studies in Svalbard - metadata and GPS tracks - Dariusz Ignatiuk; Thorben Dunse; Jean-Charles Gallet; Luc Girod; Mariusz Grabiec; Daniel Kępski; Jack Kohler; Michał Laska; Bartłomiej Luks; Ward van Pelt; Rickard Pettersson; Veijo Pohjola; et al. (Zenodo, 2022)
Surveys by ground penetrating radar (GPR) are accurate and cost-efficient, and have been conducted on Svalbard for more than 25 years, thus permitting the assessment of long term changes.The campaigns so far have covered various areas and the data is dispersed. The purpose of this report is to collect information about the conducted GPR snow cover measurements. The activities initiated in this project will be continued in the coming years and extended with a comprehensive data analysis. The dataset includes a description of metadata from GPR snow cover measurements in 1997-2022 (.CSV file) and GPS traces (.SHP files) of measurements takenin Svalbard. This study is part of the State of Environmental Science in Svalbard Report 2022 published by Svalbard Integrated Arctic Earth Observing System (SIOS).